Pendidikan Sebagai Proses Filosofis: Antara Nalar, Etika, dan Estetika - Legi, Hendrik; Devarsh Gevariel Dean Legi (PT. ALHAFI BERKAH INDONESIA, 2025)
Education as a philosophical process plays an important role in shaping individuals who have critical thinking, moral integrity, and appreciation of beauty through the integration of reason, ethics, and aesthetics. This study aims to analyze the implications of philosophical education for civilization building using descriptive qualitative methods based on the philosophy of education. Data were obtained through a literature study of philosophy of education books, academic journals, and previous research results. The analysis techniques used were content analysis and thematic analysis to understand the relationship between philosophical education and civilization. The results show that reason plays a role in developing logical, innovative and critical thinking which is the basis for the development of science and technology. Ethics acts as a moral foundation that shapes individual character to have social responsibility, honesty, and empathy in social life. Aesthetics complements education with the value of beauty and creativity that contribute to the formation of culture and art in social life. The integration of these three aspects in the curriculum allows learners to develop intellectually, morally and aesthetically so that they can make a real contribution to the development of civilization. Unbalanced education in these three aspects tends to produce individuals who lack harmony, both in thought and action. Therefore, the education system must be designed holistically so that it not only produces graduates who excel academically, but also have high morality and cultural awareness. Education based on this philosophy is expected to shape a more advanced, civilized, and dignified civilization.